2009
DOI: 10.1002/micr.20637
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic restoration of Poland's syndrome in a male patient using free anterolateral thigh perforator flap as autologous filler

Abstract: We report a case of a male patient with Poland's anomaly who was reconstructed with a free anterolateral thigh perforator flap. The flap was used successfully as an autologous filler to recreate the anterior axillary line and correct the chest contour deformity. The use of the free anterolateral thigh perforator flap is an excellent choice as an autologous filler to correct mild and moderate deformity in male Poland's syndrome, carrying low morbidity and leaving both minimal scarring and functional sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…9 Latissimus transfer in children has been reported for Poland syndrome; however, the paper only discusses the aesthetic and shoulder range of motion outcomes without mentioning objective functional outcomes of muscle transfer related to strength and function of latissimus muscle as a neo-pectoralis. 11 Unlike previously reported cases, in which an aesthetically pleasing, symmetrical chest wall was the ultimate end point, 10 we describe a technique using an ipsilateral latissimus dorsi transfer to recreate a neopectoralis major muscle for a functional outcome. The technique reported in this case provided a true functional transfer of the latissimus, with complete detachment of the native insertion and origin and creating a new origin and insertion that corresponds to the pectoralis major.…”
Section: Discussionmentioning
confidence: 94%
“…9 Latissimus transfer in children has been reported for Poland syndrome; however, the paper only discusses the aesthetic and shoulder range of motion outcomes without mentioning objective functional outcomes of muscle transfer related to strength and function of latissimus muscle as a neo-pectoralis. 11 Unlike previously reported cases, in which an aesthetically pleasing, symmetrical chest wall was the ultimate end point, 10 we describe a technique using an ipsilateral latissimus dorsi transfer to recreate a neopectoralis major muscle for a functional outcome. The technique reported in this case provided a true functional transfer of the latissimus, with complete detachment of the native insertion and origin and creating a new origin and insertion that corresponds to the pectoralis major.…”
Section: Discussionmentioning
confidence: 94%
“…They reported that this flap leaves an acceptable scar with minimal morbidity [9]. They also used de-epithelised ALT flap of 7 × 14 cm based on lateral circumflex femoral artery perforator which was moulded to give better contour.…”
Section: Discussionmentioning
confidence: 99%
“…Insertion of prosthesis under a skin flap with little subcutaneous tissue has an unnatural appearance and a higher complication rate 7 such as displacement, late seroma, discomfort, and extrusion. Contour restoration of the chest can also be obtained with deepithelialized dermal-adipose flaps or with lipofilling [8][9][10][11] without muscle transfer if the anterior axillary fold is present. Rib cartilages are often more prominent on the affected side, but reshaping is seldom necessary, particularly in women; when a breast augmentation is done, the deformation becomes less noticeable.…”
Section: Thoracic Wall Reconstructionmentioning
confidence: 99%
“…When the superior portion of the pectoralis muscle and axillary fold are present, soft tissue augmentation alone is necessary and it can be provided with a muscle, myocutaneous, cutaneous, or perforator flap, with fat grafting or with a prosthesis, depending on the quality of the overlying skin flap and the amount of breast tissue present. [8][9][10][11] The decision to harvest the ipsi-lateral latissimus dorsi muscle for volume only has to be weighed against the possible functional loss particularly in athletes. 3 When the axillary fold is missing, a dynamic muscle transfer is needed (►Fig.…”
Section: Pectoralis Muscle Reconstructionmentioning
confidence: 99%